Penerapan Prinsip Desain Tadao Ando Pada Photography Training Centre Di Pekanbaru - Sitti Fachtin Shuraha; Yohannes Firzal; Andre Novan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The advances of photography’s benefit in human life is followed by the increasing human need is used as the livelihood. Photography Training Centre is a place for training and education thatfunctioned as an interaction space for community support the creative industries in Pekanbaru. By using Tadao Ando's design principles, it is able to create interconnections photography througharchitecture and the surrounding environment. As the results of this design can be an installment for photography enthusiasts, through a concept that is triangle of exposure, this building has architectural qualities that can enhance creativity and ideas for photography through architectural elements.Keywords: Photography Training Centre, Tadao Ando, Triangle of Exposure.